Psychedelic Revolutionaries : Three Medical Pioneers, the Fall of Hallucinogenic Research and the Rise of Big Pharma - Barber, P. W. (Patrick Wayne), 1973- (Zed Books, 2018)
A fascinating investigation into a very strange episode of scientific history. P.W. Barber tells the story of the invention, practice and downfall of psychedelic psychiatry, revealing how it shaped twentieth century understanding of mental health.